Interferon-based therapy delays but metabolic comorbidity accelerates progression of chronic hepatitis C - Martínez Macías, Roberto F.; Cordero Pérez, Paula; Juárez Rodríguez, Omar A.; Chen López, Carlos Y.; Martínez Carrillo, Francisco M.; Alarcón Galván, Gabriela; Mercado Hernández, Roberto; Muñoz Espinosa, Linda Elsa (2015)
Background. We compared mortality and complications of chronic hepatitis C between treated and untreated Mexican patients after long-term follow-up. We used a time-to-event analysis and identified the prognostic factors.Material and methods. Seventy-four patients with chronic hepatitis C were studied. They were ≥ 18 years of age and had a molecular diagnosis of chronic hepatitis C and ≥ 6 months of follow-up. Patients with neoplasia or those infected with human immunodeficiency virus or hepatitis B Virus were excluded. Kaplan-Meier analysis, log-rank test, annualized incidence per 100 person-years, and stepwise discriminant analysis were used to analyse mortality and complications.Results. The end-point of annualized incidence was lowest in sustained virological responders, intermediate in non-responders, and highest in untreated patients. The absence of treatment impacted adversely on cirrhosis development and the occurrence of portal hypertension and hepatic decompensation/hepatocellular carcinoma (log-rank, p < 0.05). Diabetes impacted adversely on liver-related death/liver transplantation among untreated patients. Stepwise discriminant analysis showed that diabetes, high blood pressure, and no retreatment predicted cirrhosis development (eigenvalue ≥ 0.8; p < 0.05). A MELD score ≥ 18 and age ≥ 50 years predicted hepatic decompensation/hepatocellular carcinoma (eigenvalue < 0.8; p < 0.05). APRI ≥ 1.5 predicted mortality/liver transplantation and liver-related death/liver transplantation (eigenvalue < 0.8; p < 0.05).Conclusions. This is the first long-term study of chronic hepatitis C among Mexican patients. Treated patients showed less progression of liver disease. Treated patients showed less progression of liver disease; and older patients, those with metabolic comorbidities, with MELD score ≥ 18 and APRI ≥ 1.5 exhibited adverse effects.